FABRICS FOR BEDDING: FEATURES AND SPECIFICATIONS (Academicia Globe: Inderscience Research, 2022)
Fabrics for bed linen should create normal conditions for sleep, be harmless (fibers and preparations applied to the fabric should not emit harmful impurities). Therefore, close attention is paid to the properties of fabrics, which are indicators of the safety of textile and light industry products in accordance with the technical regulation "On the Safety of Light Industry Products". The article presents the results of studies of the influence of weaving and fibrous composition of fabrics on their hygienic and physical and mechanical properties.